When COI barcodes deceive: complete genomes reveal introgression in hairstreaks. Issue 1848 (8th February 2017) - Cong, Qian; Shen, Jinhui; Borek, Dominika; Robbins, Robert K.; Opler, Paul A.; Otwinowski, Zbyszek; Grishin, Nick V.
Abstract : Two species of hairstreak butterflies from the genus Calycopis are known in the United States: C. cecrops and C. isobeon . Analysis of mitochondrial COI barcodes of Calycopis revealed cecrops -like specimens from the eastern US with atypical barcodes that were 2.6% different from either USA species, but similar to Central American Calycopis species. To address the possibility that the specimens with atypical barcodes represent an undescribed cryptic species, we sequenced complete genomes of 27 Calycopis specimens of four species: C. cecrops, C. isobeon, C. quintana and C. bactra . Some of these specimens were collected up to 60 years ago and preserved dry in museum collections, but nonetheless produced genomes as complete as fresh samples. Phylogenetic trees reconstructed using the whole mitochondrial and nuclear genomes were incongruent. While USA Calycopis with atypical barcodes grouped with Central American species C. quintana by mitochondria, nuclear genome trees placed them within typical USA C. cecrops in agreement with morphology, suggesting mitochondrial introgression. Nuclear genomes also show introgression, especially between C. cecrops and C. isobeon . About 2.3% of each C. cecrops genome has probably ( p -value < 0.01, FDR < 0.1) introgressed from C. isobeon and about 3.4% of each C. isobeon genome may have come from C. cecrops. The introgressed regions are enriched in genes encoding transmembrane proteins, mitochondria-targeting proteins and components of the larval cuticle. This study provides the first example of mitochondrial introgression in Lepidoptera supported by complete genome sequencing. Our results caution about relying solely on COI barcodes and mitochondrial DNA for species identification or discovery.